OXCARBAZEPINE-INDUCED HYPONATREMIA IN METABOLIC ENCEPHALOPATHY: A CASE REPORT - AMRITHA CHANDRASEKARAN SASHIKAR; ANGELIN GRACE T; ANN JENCY A; DHIVYAPRASATH P (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The 81-year-old woman in this instance had a 3-day history of diminished sensorium and was suffering from significant left ventricular dysfunction, osteoporosis, uterine malignancy, and a history of nephrectomy, among other chronic illnesses. Medication for heart failure, neuropathic pain, anemia, and fluid retention were all part of her treatment plan. Along with careful monitoring of electrolytes and renal function, the patient was treated with a mixture of pregabalin, clonazepam, carvedilol, atorvastatin, spironolactone, and other supplements. The patient’s usage of oxcarbazepine, a medication known to create electrolyte imbalances and antidiuretic effects, is probably what caused her to develop hyponatremia. Using the Naranjo adverse drug response probability scale, a causality evaluation revealed a “probable” adverse drug response with a score of 7, indicating a probable connection between her electrolyte imbalance and oxcarbazepine.